A review of emerging techniques for pyrethroid residue detection in agricultural commodities - Goh, Dirong; Abdull Razis, Ahmad Faizal; Yusof, Nor Azah; Mazlan, Norida; Nordin, Noordiana; Yu, Choo Yee (Elsevier, 2025)
Pyrethroid pesticides are essential for modern agriculture, helping to control pests and protect crops. However, due to growing concerns about their potential impact on human health and the environment, reliable detection methods are essential to ensure food safety. In this literature review, we explore the techniques used over the past decade to detect pyrethroid residues in agricultural products. Until now, various methods have been developed for detecting pyrethroid pesticides, ranging from conventional analytical approaches to innovative approaches. The conventional analytical approaches include gas, liquid, and supercritical fluid chromatography, micellar electrokinetic capillary chromatography, and enzyme-linked immunosorbent assay. Whereas innovative approaches refer to various optical-based and electrochemical-based sensors. For each method, we evaluate its strengths, limitations, and practical applications. Recent innovations are highlighted, focusing on sensitivity, selectivity, and practical applicability. By summarizing the current state of research, this review serves as a valuable resource for researchers and practitioners, providing insights into the evolving technology and strategy for detecting pyrethroid residue.